Association of hepatic oxidative stress and iron dysregulation with HCC development after interferon therapy in chronic hepatitis C. Issue 3 (19th August 2015) - Nanba, Shintaro; Ikeda, Fusao; Baba, Nobuyuki; Takaguchi, Koichi; Senoh, Tomonori; Nagano, Takuya; Seki, Hiroyuki; Takeuchi, Yasuto; Moritou, Yuki; Yasunaka, Tetsuya; Ohnishi, Hideki; Miyake, Yasuhiro; et al.
Abstract : Background: Oxidative stress may play pathogenic roles in the mechanisms underlying chronic hepatitis C (CHC). The impact of excessive oxidative stress and iron dysregulation on the development of hepatocellular carcinoma (HCC) after interferon therapy has not been established. Methods: We investigated the impact of oxidative stress and iron deposition on HCC development after therapy with pegylated interferon (PegIFN)+ribavirin in CHC patients. Systemic and intracellular iron homeostasis was evaluated in liver tissues, peripheral blood mononuclear cells and sera. Results: Of 203 patients enrolled, 13 developed HCC during the 5.6-year follow-up. High hepatic 8-hydroxy-2-deoxyguanosine (8-OHdG) levels were significantly associated with HCC development in multivariate analysis (p=0.0012) which was also significantly correlated with severity of hepatic iron deposition before therapy (p<0.0001). Systemic and intracellular iron regulators of hepcidin and F-box and leucine-rich repeat protein 5 (FBXL5) expression levels were significantly suppressed in CHC patients (p=0.0032 and p=0.016, respectively) despite their significantly higher levels of serum iron and ferritin compared with controls. However, intracellular iron regulators of FBXL5 and iron regulatory proteins were regulated in balance with hepatic iron deposition. Significant correlations were observed among IL-6, bone morphogenetic protein 6, hepcidin and ferroportin, as regards systemic iron regulation. Conclusions: Measurement of hepatic oxidative stress before antiviral therapy is useful for the prediction of HCC development after interferon therapy. Low baseline levels of the intracellular iron regulators of FBXL5 in addition to a suppressed hepcidin level might be associated with severe hepatic iron deposition in CHC patients. Trial registration number: UMIN 000001031.